Ultrasonographic diagnosis of pregnancy in the mare - YPSILANTIS (Π. ΥΨΗΛΑΝΤΗΣ), P. (Journal of the Hellenic Veterinary Medical Society, 2018)
The ultrasonographic examination of the uterus makes early pregnancy diagnosis in the mare possible by day 9 (day 0: day of ovulation). After a brief description of the examination procedure and a report on some anatomical and embryological features of the horse, the ultrasonographic findings at different stages of pregnancy, as well as those of twin pregnancy are described. Pregnancy findings are differentiated from pathological ones. Finally, the method is evaluated based on its advantages and disadvantages.